Development of Interactive Learning Media Assisted by Websites for Intensive Reading in Grade IV of Elementary School - Salshabilla Fitri; Elfis Sukma (Journal of English Language and Education, 2026)
This study was motivated by the low intensive reading ability of fourth-grade elementary school students and the limited use of technology-based learning media in Indonesian language learning. The purpose of this study was to develop an interactive learning media assisted by a website to improve students' intensive reading skills. This research used a Research and Development method with the ADDIE development model consisting of analysis, design, development, implementation, and evaluation stages. The subjects of this study were fourth-grade students in several elementary schools in Payakumbuh City. The product developed was an interactive website-based learning media containing learning materials, instructional videos, quizzes, and evaluation activities. The validation results from material, language, and media experts showed an average validity score of 90%, which indicated that the product was very valid. The practicality test showed that the teacher response reached 86% and the student response reached 82.53%, both categorized as very practical. The effectiveness test also indicated an improvement in students' learning outcomes after using the developed media. Therefore, the website-assisted interactive learning media was considered valid, practical, and effective for use in intensive reading learning for fourth-grade elementary school students.